INDO-EUROPEAN AND EUROPEAN IMAGES IN PERANAKAN CHINESE LITERATURE - Dwi Susanto (KAJIAN SASTRA, 2010)
This paper aims to explore images of Indo European and European in peranakan Chinese literature. This paper uses the paradigm that literature is objective of mind as result from action of thinking. Literary works which are used as main data will interpret in term of historical context. So, this paper contains intellectual history which focused the viewing toward Western on the Chinese intellectual minds. The paper will explore and give answers about (1) how they represent European and Indo-European in their minds (2) why they represent the European and Indo-European, and (3) how the impact of political and vision of the authors in their works. Based on literary works and historical context, the phenomenon of literary works will bring into interpretation between spirit of age and topic of European and Indo European images in their literary works